Direct and Indirect Factors Influencing Cat Outcomes at an Animal Shelter - Kilgour, R. J.; Flockhart, D. T. T. (Frontiers in Veterinary Science, 2022)
Animal shelters play a vital role for pets, transitioning animals between homes, from outdoor communities into homes, caring for unadoptable and community animals, and providing a breadth of veterinary and welfare services. The goal of shelters is to move cats to their appropriate outcome as quickly as possible, which for many animals, is to rehome them as quickly as possible through adoption. Therefore, the ability to identify pre-existing factors which result in adoption (or other outcomes) is vital. In this study, we used structural equation modelling to test four hypotheses addressing how to predict cat outcome from a shelter in Washington, D.C. We developed four hypotheses that described how cat outcomes could be predicted, based on four general factors: 1. The characteristics of the cats; 2. The location of origin; 3. The type and date of intake; 4. The length of stay. Using four years of data from the Humane Rescue Alliance in Washington, D.C., we found support for each of our hypotheses. Additionally, we tested and found support for a global model, which comprised an amalgamation of our all our predictors. From the global model, we can conclude that many factors are at play in predicting cat outcomes in this shelter and very likely in many others as well. Critically, these factors are interconnected. Furthermore, our study highlights the importance of incorporating influences beyond the shelter when attempting to understand cat outcomes. Therefore, to modify cat outcomes most efficiently, such as increasing adoption probabilities, our results show that efforts may be most effective when incorporating multiple factors, given the complexity in predicting shelter outcomes.